Identifying effective intervention components for smoking cessation: a factorial screening experiment. (19th November 2015) - Piper, Megan E.; Fiore, Michael C.; Smith, Stevens S.; Fraser, David; Bolt, Daniel M.; Collins, Linda M.; Mermelstein, Robin; Schlam, Tanya R.; Cook, Jessica W.; Jorenby, Douglas E.; Loh, Wei‐Yin; Baker, Timothy B.
Abstract: Aims : To identify promising intervention components intended to help smokers to attain and maintain abstinence in their quit smoking attempts. Design: A fully crossed, six‐factor randomized fractional factorial experiment. Setting: Eleven primary care clinics in southern Wisconsin, USA. Participants: A total of 637 adult smokers (55% women, 88% white) motivated to quit smoking who visited primary care clinics. Interventions: Six intervention components designed to prepare smokers to quit, and achieve and maintain abstinence (i.e. for the preparation, cessation and maintenance phases of smoking treatment): (1) preparation nicotine patch versus none; (2) preparation nicotine gum versus none; (3) preparation counseling versus none; (4) intensive cessation in‐person counseling versus minimal; (5) intensive cessation telephone counseling versus minimal; and (6) 16 versus 8 weeks of combination nicotine replacement therapy (nicotine patch  +  nicotine gum). Measurements: Seven‐day self‐reported point‐prevalence abstinence at 16 weeks. Findings: Preparation counseling significantly improved week 16 abstinence rates ( P = .04), while both forms of preparation nicotine replacement therapy interacted synergistically with intensive cessation in‐person counseling ( P  < 0.05). Conversely, intensive cessation phone counseling and intensive cessation in‐person counseling interacted antagonistically ( P  < 0.05)—these components produced higher abstinence rates by themselves than in combination. Conclusions: Preparation counseling and the combination of intensive cessation in‐person counseling with preparation nicotine gum or patch are promising intervention components for smoking and should be evaluated as an integrated treatment package.